On the application of public search measures to detect and obtain information - Цільмак, Олена Миколаївна; Цільмак, О. М.; Цильмак, Елена Николаевна; Tsilmak, Olena M.; Козицька, Олена Геннадіївна; Козицька, О. Г.; Козицкая, Елена Геннадиевна; Kozytska, Olena H.; Проценко, Олена Олександрівна; Проценко, О. О.; Проценко, Елена Александровна; Protsenko, Olena O.; et al. (IJCSNS, 2021)
The article considers the state of legislation that regulates the use of public methods of obtaining information by authorized state bodies. The correlation of public investigative (search) actions with operative-search measures as concepts denoting the application of public methods of obtaining information has been studied. In addition, it argues the need for more detailed delineation and legislative regulation of public investigative (search) actions and operational and investigative measures at the legislative and departmental levels. The purpose of the article is to analyze certain provisions of the Law of Ukraine "On operational and investigative activities" to identify inconsistencies in the content of the text of the law in order to correct and prevent ambiguity in the theory and practice of law enforcement.

У статті розглянуто стан законодавства, яке регулює використання публічних методів отримання інформації шляхом уповноважених державних органів. Досліджено співвідношення публічних слідчих (розшукових) дій з оперативно-розшуковими заходами як поняття, що позначають застосування публічних способів одержання інформації. Метою статті є аналіз окремих положень Закону України «Про оперативно-розшукову діяльність» для виявлення невідповідностей у змісті тексту закону з метою виправлення та запобігання двозначності в теорії та практиці правозастосовної діяльності.
Kozytska O. On the application of public search measures to detect and obtain information / O. Kozytska, O. Tsilmak, O. Protsenko, M. Yankovyi, А. Lysenko, A. Shulzhenko // International Journal of Computer Science and Network Security.– Vol. 21. - № 9. – IJCSNS, 2021. - P. 109-112.
Keywords: operative-search activity; operative-search measures; public procedural activity; information; оперативно-розшукова діяльність; оперативно-розшукові заходи; публічно-процесуальна діяльність; інформація; Research Subject Categories::LAW/JURISPRUDENCE